2018
DOI: 10.3382/ps/pey202
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of paddy rice increases intestinal mucin secretion and goblet cell number and prevents dextran sodium sulfate-induced intestinal barrier defect in chickens

Abstract: Paddy rice is a potential feed grain for chickens, whose strong gizzards can crush the hull. Here, we investigated whether paddy rice rich in hull-derived water-insoluble dietary fiber stimulates intestinal mucin secretion and production, as well as the possible involvement of paddy rice in intestinal barrier function. Layer male chicks at 7 d of age were divided into four groups according to the diet: corn, polished rice, brown rice, or paddy rice (650 g/kg diet), which they ate for 14 consecutive days. At 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The results of our research showed that administration of S. jaoensis increased the number and area of goblet cells (Table-4), suggesting that mucin production in the small intestine is higher in the treatment groups. Elevated intestinal mucin along with higher epithelial turnover may increase the effectiveness of the small intestine in nutrient absorption [42].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our research showed that administration of S. jaoensis increased the number and area of goblet cells (Table-4), suggesting that mucin production in the small intestine is higher in the treatment groups. Elevated intestinal mucin along with higher epithelial turnover may increase the effectiveness of the small intestine in nutrient absorption [42].…”
Section: Discussionmentioning
confidence: 99%
“…Permeability in the ileum and cecum was examined using fluorescein isothiocyanate (FITC) -labeled dextran with a molecular weight of 4,000 (FD-4, Sigma Aldrich, St Louis MO, USA) and a modified version of the protocol outlined by Murai et al (2018). The ileum and cecum were cut into sections of approximately 3 cm, inverted, closed with a string on one side, and filled with oxygen aerated Tyrode's bal-…”
Section: Gut Permeability Testmentioning
confidence: 99%
“…Moreover, it has been shown that dietary restriction can lead to regression in mucosal development ( Uni et al., 1998 ) while MUC2 mRNA expression is reduced in intestine of germ-free birds ( Cheled-Shoval et al., 2014 ) suggesting a role of the bacterial population in mucus development. Because of the undeveloped gut barrier and immune system immediately after hatch, presence of mucus is important for gut protection during the first hours post-hatch ( Moreira Filho et al., 2019 ) and it has been suggested that enhancement of mucin secretion in young chickens during the development of the gut mucosal barrier could be beneficial in preventing the invasion of pathogenic bacteria and toxins ( Murai et al., 2018 ). Lack of feed for the first 48 h seems to have a deteriorating effect on the chicks' ability to protect itself from pathogenic bacteria and toxins.…”
Section: Discussionmentioning
confidence: 99%